Does gender matter for green behaviour: An empirical investigation with cross-country data from the Enterprise Surveys - Camilla Jensen (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2023)
Using firm-level data from the World Bank's Enterprise Surveys, the paper investigates, across 8 European and Central Asian countries, the hypothesis that female entrepreneurs are more likely to exhibit green behaviour, by adopting new and more environmentally friendly and/or energy efficient technologies (ecopreneurship). Across several dependent variables, it is shown that women demonstrate a higher propensity to act in such ecopreneurial ways. However, it is a paradox, that for the former socialist country part of the sample, gender has been mainstreamed, in terms of both ownership and management shares (approaching gender equality or neutrality in firms), but this does not have an overall positive impact on greening the technology adoption rates. The study shows that, as gender participation is mainstreamed, or by subjecting traditional female values to male institutions of professional management, so is behaviour.
Keywords: 330; Unternehmerinnen; Unternehmer; Umwelttechnik; Innovationsakzeptanz; Europa; Zentralasien